Factors affecting arteriovenous access patency after percutaneous transluminal angioplasty in chronic haemodialysis patients under vascular access monitoring and surveillance: a single-centre observational study - Chung-Kuan Wu; Der-Cherng Tarng; Chia-Hsun Lin; Jyh-Gang Leu; Chih-Yu Yang (BMJ Open)
Objectives Maintenance of vascular access (VA) patency after percutaneous transluminal angioplasty (PTA) is important and remains a challenge despite VA monitoring and surveillance. The aim of this study was to examine factors affecting the post-PTA arteriovenous access (AVA) patency in patients who have been on close VA monitoring and surveillance for access flow.Design Retrospective cohort study.Setting A single medical centre in Taiwan.Participants Records of patients who received chronic haemodialysis between 1 January 2017 and 31 December 2018 were retrospectively reviewed. Patients were divided into two groups (without or with PTA intervention on AVA).Primary and secondary outcome Patients were followed until reintervention PTA, termination or abandoned VA or end of study. In addition to routine monitoring, VA flow surveillance was performed every 3 months for detection of VA dysfunction adhering to Kidney Disease Outcomes Quality Initiative guidelines.Results A total of 508 patients were selected for study inclusion (with PTA, n=231; without PTA, n=277). At baseline, variables that differed between groups included malignancy and levels of albumin, uric acid, potassium, phosphorous, high-density lipoprotein, total bilirubin and ferritin (all p<0.05). Significant between-group differences were observed for β-adrenergic blocking agents (with PTA, 49.8%; without PTA, 37.5%; p, 0.007) and ADP inhibitors (with PTA, 23.8%; without PTA, 11.2%; p<0.001). Among patients with PTA, those with acute myocardial infarction, high ferritin level or arteriovenous graft (AVG) had a significantly higher risk of reintervention post-PTA (p<0.05). Dipeptidyl peptidase-4 inhibitors, thiazolidinediones, ADP inhibitors, and warfarin use were predictors of post-PTA patency (p<0.05).Conclusions AVG access type, acute myocardial infarction, and high ferritin levels are risk factors for re-intervention post-PTA. These findings may be useful in the development of prophylactic strategies for monitoring VA function and tailoring surveillance programs for these dialysis patients.